A high performance wire-shaped flexible lithium-ion battery based on silicon nanoparticles within polypyrrole/twisted carbon fibers. Issue 43 (17th May 2017) - Rao, Jiangyu; Liu, Nishuang; Li, Luying; Su, Jun; Long, Fei; Zou, Zhengguang; Gao, Yihua
Abstract : Interconnected Si/PPy/CF electrode was made by in situ polymerization method and used in the wire-shaped lithium ion battery. The electrode exhibited superior electrochemical properties and flexible ability. Abstract : Currently, mechanically flexible and strong batteries are desired for the development of bendable and portable devices. To meet this requirement, a simple and scalable synthesis of the anode for flexible wire-shaped lithium-ion batteries has been developed by a facile one-step in situ polymerization method. Polypyrrole was found to grow on the surface of Si nanoparticles and attach to twisted carbon fibers. The formed cross-linked structure of Si/PPy along with carbon fiber substrate offers a consecutive electron transport network and a porous structure to adjust large volumetric changes of Si particles during charging and discharging processes. On fabricating the wire-shaped Li-ion battery, the interconnected Si/PPy/CF hybrid electrode was found to offer an excellent performance of 3.9% capacity decrease after the flexibility test, a greatly improved cycling capacity of 2287 mA h g −1 and a capacity retention of about 75% after 100 cycles of the half-cell test. The all-wet methodology may provide a promising route for a new scalable way to produce applicable wire-shaped electrode in battery fabrication.